Landscapes and landforms of Italy - Soldati, Mauro; Marchetti, Mauro (World geomorphological landscapes., 2017)
The book deals with the most striking landscapes and landforms of Italy. Attention is given to landform diversity and landscape evolution through time which has been controlled by very diverse geological conditions and dramatic climate changes that have characterized the Italian peninsula and islands since the end of the last glaciation. In addition, various examples of human impact on the landscape are presented. Landscapes and Landforms of Italy contains more than thirty case studies of a multitude of Italian geographical landmarks. The topics and sites described in this book range from the Alpine glaciers to the Etna and Vesuvius volcanoes, taking into account the most representative fluvial, coastal, gravity-induced, karst and structural landscapes of the country. Chapters on the geomorphological landmarks of the cities of Rome and Venice are also included. The book provides the readers with the opportunity to explore the variety of Italian landscapes and landforms through informative texts illustrated with several color maps and photos. This book will be relevant to scientists, scholars and any readers interested in geology, physical geography, geomorphology, landscape tourism, geoheritage and environmental protection.- Resumé vydavatel